Advances in phage display based nano immunosensors for cholera toxin - Li, Yang; Yang, Kai-di; Kong, De-cai; Ye, Jun-feng (Frontiers in Immunology, 2023)
Cholera, a persistent global public health concern, continues to cause outbreaks in approximately 30 countries and territories this year. The imperative to safeguard water sources and food from Vibrio cholerae, the causative pathogen, remains urgent. The bacterium is mainly disseminated via ingestion of contaminated water or food. Despite the plate method's gold standard status for detection, its time-consuming nature, taking several days to provide results, remains a challenge. The emergence of novel virulence serotypes raises public health concerns, potentially compromising existing detection methods. Hence, exploiting Vibrio cholerae toxin testing holds promise due to its inherent stability. Immunobiosensors, leveraging antibody specificity and sensitivity, present formidable tools for detecting diverse small molecules, encompassing drugs, hormones, toxins, and environmental pollutants. This review explores cholera toxin detection, highlighting phage display-based nano immunosensors' potential. Engineered bacteriophages exhibit exceptional cholera toxin affinity, through specific antibody fragments or mimotopes, enabling precise quantification. This innovative approach promises to reshape cholera toxin detection, offering an alternative to animal-derived methods. Harnessing engineered bacteriophages aligns with ethical detection and emphasizes sensitivity and accuracy, a pivotal stride in the evolution of detection strategies. This review primarily introduces recent advancements in phage display-based nano immunosensors for cholera toxin, encompassing technical aspects, current challenges, and future prospects.